Supplementary description of floral characters and nomenclatural note for the rare maple Acer yui W.P.Fang (Sapindaceae) from western China - Liu, Fu-Rong; Wang, Hai-Feng; Peng, Pei-Hao; Luo, Jian-Xun (Phytotaxa, 2022)
The floral characters of Acer yui are supplemented based on living plants flowering in April from the type locality. It is distinguishable based on both vegetative and floral characters between the two morphologically similar species, A. buergerianum and A. yui. Contrary to general consideration that the holotype is at PE, A. yui did not have a holotype designated when being described. It was later inadvertently lectotypified by Fang in 1939 and the single specimen traced meets that designation should be the lectotype, and the other duplicates are isolectotypes.